Assessing the Response of the Global South to Russo-Ukrainian War: Case Study of India - Alfin Febrian Basundoro; Muhammad Irsyad Abrar; Trystanto Trystanto (Global South Review, 2022)
The Russian invasion of Ukraine on February 24, 2022, resulted in a prolonged war between the two countries. It creates a worldwide geoeconomic impact, including stagflation due to the disruption of the supply chains, profoundly affecting the economies of Global South countries. Additionally, the aggression contradicts the principles of sovereignty, territorial integrity, and independence that the Global South countries hold dear (United Nations, 2015). Despite these, most Global South countries, including India, refused to condemn Russia for its actions, except for the UN General Assembly vote to condemn Russia on March 2. This situation begs the question: Why would not India, one of the significant Global South countries, blame Russia for its detrimental actions to the ideals of the Global South? We argue that when national interests and values come into conflict, Global South countries may prioritize their interest rather than uphold the values deeply held by the Global South—a vindication that Realpolitik still held preeminence within the foreign policymaking of the Global South countries, including India. This is evident in India's response to the Russian aggression, as India still maintains a strategic partnership with Russia even after Russia tramples the values of the Global South via its war in Ukraine. At the same time, India tries to avoid being engaged closely with Russia as India still needs the support of the United States to balance China's geopolitical moves, given India's territorial disputes with China.